L’Open space ou comment les jeux de pouvoir engendrent de nouvelles formes de micro-territorialités dans les bâtiments intelligents - Amélie Coulbaut-Lazzarini; Guillaume Bailly (L'Espace Politique)
This paper studies new socio-spatial segregation modalities within tertiary buildings through a micro geographical perspective. In our fieldwork, multinational firms have a strong hierarchical weight and can be seen as quasi-totalitarian organisations like prisons or asylums, representative of a powerful socio-spatial control. The paper analyses how uses in those buildings have an impact on spatial practices. It shows how these practices are correlated with dominant representations of people’s roles and positions. It also demonstrates how constraints, social control and spatial organisation lead people to innovate and appropriate new spaces, and how this new spatial use build new territorialities. Lastly, through thematic programs about energy efficiency, the paper shows the establishment of new social links and new spatial relations driven by a cooperation spirit in order to achieve the common objectives of energy efficiency program.